Double Barreled Wet Colostomy: Initial Experience and Literature Review - Luis Salgado-Cruz; Eloy Espin-Basany; Francesc Vallribera-Valls; Jose Sanchez-Garcia; Luis Miguel Jimenez-Gomez; Marc Marti-Gallostra; Ana Garza-Maldonado (The Scientific World Journal)
Background. Pelvic exenteration and multivisceral resection in colorectal have been described as a curative and palliative intervention. Urinary tract reconstruction in a pelvic exenteration is achieved in most cases with an ileal conduit of Bricker, although different urinary reservoirs have been described. Methods. A retrospective and observational study of six patients who underwent a pelvic exenteration and urinary tract reconstruction with a double barreled wet colostomy (DBWC) was done, describing the preoperative diagnosis, the indication for the pelvic exenteration, the complications associated with the procedure, and the followup in a period of 5 years. A literature review of the case series reported of the technique was performed. Results. Six patients had a urinary tract reconstruction with the DBWC technique, 5 male patients and one female patient. Age range was from 20 to 77 years, with a medium age 53.6 years. The most frequent complication presented was a pelvic abscess in 3 patients (42.85%); all complications could be resolved with a conservative treatment. Conclusion. In the group of our patients with pelvic exenteration and urinary tract reconstruction with a DBWC, it is a safe procedure and well tolerated by the patients, and most of the complications can be resolved with conservative treatment.